Climate Change and Displacement: Learning from Resettlement in the Development Context. (March 2015) - Mathur, Hari Mohan
Climate change is expected to eventually affect hundreds and millions of people and they will require resettlement, since their existing habitations will no longer remain liveable. Resettlement as a response to climate change impacts (or an adaptation strategy) is now becoming increasingly acceptable. But for humanitarian agencies, essentially focused on protecting and assisting the victims of human rights abuses, resettlement is an unchartered territory. They can, however, learn much from resettlement experience of development agencies, international as well as national. This article presents resettlement experience associated with development projects, its strengths and weaknesses, and looks at its implications for planning climate change resettlement.